Hipersensibilidad a medicamentos en enfermedades del tejido conectivo - Della Pina, Armando Silicani (1978)
One hundred and thirty patients with ccective tissue diseases were evaluated in the Departament of Medine; the main purpose was to to flind out, the frequency of drug hypersensitivity in these patients. A clinical criteria for the diagnosis was used.  Drug hypersensitivity was more frequently found in the connective tissue diseases than in the control group; particularly in Systemic Lupus Erithematosus. Some cases of hypersensitivity abfeitis and Schönlein-Henoch purpura were precipitated by drug hypersensitivity. Penicillin. Sulphamethoxipiridozine and Dilantin were the most common offenders.  There were negative L.E cells and also negative antinuclear antibodies, in drug hypersensitivity not related to connective tissue diseases.  The abuse in the use of drugs must be avoided and it would be wise to have an effective control at a national level.  It was proposed the blastic transformation of lymphocytes and the lymphocytes migrating inhibitor factor technics to make the diagnosis of drug hypersensitivity.